Wound breakdown after middle cranial fossa craniotomy: An unusual complication after rhytidectomy. (22nd October 2013) - Moberly, Aaron C.; Tweel, Benjamin C.; Welling, D. Bradley
<x xml:space="preserve">Abstract</x> Wound complications after middle cranial fossa craniotomy are rare. We describe a patient who underwent a left middle fossa craniotomy for resection of a small internal auditory canal tumor with subsequent development of wound breakdown and infection 1 week postoperatively. Prompting of the patient elicited a history of bilateral rhytidectomies. Wound debridement, hyperbaric oxygen therapy, dermal regeneration template placement, and prolonged antibiotic treatment were performed. Complete secondary intention healing occurred with an acceptable cosmetic outcome. Prior rhytidectomy scars must be identified and incorporated into the surgical planning prior to performing middle fossa craniotomy incisions. Laryngoscope, 124:554–557, 2014